Effects of Lactobacillus Probiotic, P22 Bacteriophage and Salmonella Typhimurium on the Heterophilic Burst Activity of Broiler Chickens - Marietto-gonçalves, Ga [UNESP]; Smr, Curotto; Baptista, Aas [UNESP]; Donato, Tc [UNESP]; Takahira, Rk [UNESP]; Sequeira, Jl [UNESP]; Andreatti Filho, Rl [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2014)
Due to the constant evolution of industrial poultry production and the global emergence of bacterial resistance to antibiotics there has been an increasing interest in alternatives for the treatment of poultry salmonellosis, such as phage therapy and probiotics. The present study evaluated the effects of the oral administration of the bacteriophage P22 and of a probiotic, consisting of four Lactobacillus species, on the level of circulating heterophils containing a superoxide anion of one-day-old broilers challenged with Salmonella Typhimurium for seven days. It was concluded that the treatment with a probiotic with lactobacilli of broilers experimentally infected with Salmonella spp eliminates this pathogen by increasing the circulating levels of reactive heterophils. When chicks are treated with a probiotic and a bacteriophage, the agent is eliminated with no changes in circulating reactive heterophil counts. It is also concluded that the heterophils of day-old chicks are not capable of producing superoxide anion. However, this capacity is detected after 48 h of life, indicating that heterophils mature as birds age.
Keywords: Salmonellosis; immune response; respiratory burst; poultry